2018
DOI: 10.48550/arxiv.1802.01672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entrance and exit at infinity for stable jump diffusions

Abstract: In his seminal work from the 1950s, William Feller classified all one-dimensional diffusions on −∞ ≤ a < b ≤ ∞ in terms of their ability to access the boundary (Feller's test for explosions) and to enter the interior from the boundary. Feller's technique is restricted to diffusion processes as the corresponding differential generators allow explicit computations and the use of Hille-Yosida theory. In the present article we study exit and entrance from infinity for the most natural generalization, that is, jump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Actually, the above condition implies that the associated CB-process with competition in a Lévy random environment comes down from infinity. This phenomenon has been observed and studied by several authors in branching processes with interactions, see for instance González-Casanova et al [12], Lambert [18], Li [23], Li et al [24] and Pardoux [28] and also for stable jump diffusions by Döring and Kyprianuo [9] and some jump diffusions by Bansaye [4]. Formally, we define the property of coming down from infinity in the sense that ∞ is a continuous entrance point, i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Actually, the above condition implies that the associated CB-process with competition in a Lévy random environment comes down from infinity. This phenomenon has been observed and studied by several authors in branching processes with interactions, see for instance González-Casanova et al [12], Lambert [18], Li [23], Li et al [24] and Pardoux [28] and also for stable jump diffusions by Döring and Kyprianuo [9] and some jump diffusions by Bansaye [4]. Formally, we define the property of coming down from infinity in the sense that ∞ is a continuous entrance point, i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 97%
“…where T M = inf{t ≥ 0 : Z t ≤ M } and the original process can be extended into a Feller process on [0, ∞] (see for instance Theorem 20.13 in Kallenberg [15] for the diffusion case or Definition 2.2 for Feller processes in [9]).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…and the original process can be extended into a Feller process on [0, ∞] (see for instance Theorem 20.13 in Kallenberg [11] for the diffusion case or Definition 2.2 for Feller processes in [4]).…”
Section: General Casementioning
confidence: 99%
“…Indeed, the authors showed that the killing time is finite almost surely and the left-limit at the killing time is 0. Applications of the conditioned processes have been found for instance in the study of entrance and exit at infinity of stochastic differential equations driven by stable processes, see Döring and Kyprianou [7].…”
Section: Introductionmentioning
confidence: 99%